Examinando os papéis do sexo, identidade de gênero e tempo de diagnóstico na camuflagem social no transtorno do espectro do autismo - Cassaguerra, Bianca Fernandes (Universidade Federal de São Carlos, 2024)
The diagnosis of Autism Spectrum Disorder (ASD) is given three to four times more for men than for women, because, according to the literature in the area, women must express more behavioral problems and emotional deficits than men to receive the diagnosis. Furthermore, even though they have similar degrees of autistic traits, women are diagnosed later than men. A theory that proposes to explain the reason for this difference is that of social camouflage, which refers to a strategy, consciously or unconsciously acquired, used by people on the autistic spectrum to fit into a social context and involves the act from disguising typical autism behaviors to becoming more like a typical neuro person. The aim of this study will be to investigate the roles of sex, gender identity (gender diverse versus cisgender) and time of diagnosis (diagnosed in childhood or adolescence versus in adulthood) and the interactions between these factors in Brazilian adults diagnosed with ASD. Participants will be 30 adults over 18 years of age diagnosed with ASD by medical report of both biological sexes and any gender identity (for example, cis woman, cis man, trans woman, trans man, etc.). A sociodemographic questionnaire and the Camouflaging Autistic Traits Questionnaire (CAT-Q) translated into Portuguese will be used, both applied via Google Forms. Then, a semi-structured interview will be conducted with questions about the participant's experience with ASD, conducted through Google Meet. During the interviews, participants reported as relevant factors related to social camouflage, the diagnostic process, sensory sensitivities, social interactions, difficulties related to educational institutions and the job market, and other issues such as bullying, abusive relationships, sexuality, gender, and self-stigmatization. In the CAT-Q, the ten highest scores were from biologically female participants. Among these ten participants, eight identify as cisgender women. The individuals with the highest scores were female, non-heterosexual, of diverse gender, with incomplete higher education, and who received the diagnosis after the age of 21. Although these findings are consistent with what is found in the literature, the results of the analysis of covariance (ANCOVA) based on p-values indicate that none of the categories had a differentiated impact on social camouflage strategies, nor on the subcategories of compensation, masking, and assimilation (significance would be indicated for p-values < 0.05). Additionally, the effect size of these categories on social camouflage is low (η² < 0.07 for all analyses). These results differ from those found in the literature.
Examining the roles of sex, gender identity and diagnostic time on social camouflage in autism spectrum disorder
Keywords: Transtorno do espectro do autismo; Autism spectrum disorder; Diagnóstico tardio; Late diagnosis; Camuflagem social; Social camouflage; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO